The effect of palm oil fuel ash (POFA) as a partial cement replacement towards the formation of delayed ettringite formation (DEF) in concrete - Mimi Syahida, Muhamad (2015)
Malaysia is one of the largest producers of palm oil and the amount of waste generated by the palm oil plant increasing from day to day. Due to the increasing of waste, a lot of research has been done to recycle palm oil fuel ash (POFA) utilization in Malaysia as construction material to replace ordinary Portland cement (OPC). The utilization of POFA which is generated by the residual of Malaysian palm oil industry can produced a new construction material. It is one of the solutions to reduce the quantity of POFA disposed at landfills. This study was focus on the delayed ettringite formation (DEF), compressive strength and microstructure of concrete containing POFA. Four types of mixes are prepared. The percentage of POFA used was 0%, 10%, 20% and 30% as a partial cement replacement. The concrete cured for 7, 28 and 90 days were tested for the compressive strength. The specimens of 0% and 20% of POFA at 28 days and 90 days were testing for microstructure by using Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) test. All specimens were tested for DEF after heated about 90 days. From the results obtained, the compressive strength of the concrete for 10%, 20% and 30% produced slightly lower than the control mix (0%) at each of age curing period. Specimen with 30% of POFA produced the lowest compressive strength compared to the others. The maximum compressive strength was determined for control mix (0% of POFA) about 29.349 MPa. This shows that the 20% POFA replacement for cement produces the optimum compressive strength results. The results generated from XRD test shows that at 29.411(deg) is the peak of C-S-H for 0% of POFA and 29.546 (deg) is the peak of C-S-H for 20% of POFA at 90 days. It shows that reaction occur in concrete. The image generated from (SEM) shows the microstructure of the POFA in concrete. The samples do not generate a lot of momentous, so the images are not as clear as metals at high magnifications. 0% of POFA shows larger extend and size ettringite needles (2μm) while on the 10% to 30% of POFA substitution concrete, the needles’ size are 1μm. As a conclusion, POFA can be used as a replacement of cement in concrete. The use of finer pozzolan as a partial cement replacement can be eliminated the formation of ettringite and better effect to the concrete. POFA can be used as an alternative material in concrete because it has pozzolanic characteristic prove the reaction in the hydration process.